Wherever you are : my love will find you - Tillman, Nancy (New York : Feiwel and Friends, 2010)
Offers reassurance to children about the strength, depth, and endurance of the love their parents have for them.
Booklist, September 2010.
Horn Book, May 2011.
Booklist.
Horn Book.
1.5
K-3
Keywords: Love -- Juvenile fiction; Parent and child -- Juvenile fiction; Love -- Fiction; Parent and child -- Fiction; Stories in rhyme; Love -- Fiction; Parent-child relationship -- Fiction; Stories in rhyme; Stories in rhyme; Love -- Fiction; Parent and child -- Fiction; Animals -- Fiction; Picture books for children